2016
DOI: 10.1016/j.ijsu.2015.12.045
|View full text |Cite
|
Sign up to set email alerts
|

“Pure” large cell neuroendocrine carcinoma of the gallbladder. Report of a case and review of the literature

Abstract: a b s t r a c tPrimary Neuroendocrine Tumours (NETs) of the gallbladder are rare. Among all NETs of the gallbladder, large cell neuroendocrine carcinoma (LCNEC) is exceedingly rare. In most of the cases LCNECs are combined with other histological components. We reviewed clinical presentation and management of all patients with "pure" LCNEC from published literature since the first case was published in 2000, as well as one patient from our experience. Only 7 cases of "pure" LCNEC has been described in the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
(23 reference statements)
0
28
0
Order By: Relevance
“…Preoperative diagnosis of NETs of the gallbladder is rare because, in general, the patients present with non-specific symptoms such as upper abdominal pain, discomfort, jaundice, and weight loss [ 18 ]. Previous studies showed that few cases of gallbladder NETs manifested with carcinoid syndrome [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative diagnosis of NETs of the gallbladder is rare because, in general, the patients present with non-specific symptoms such as upper abdominal pain, discomfort, jaundice, and weight loss [ 18 ]. Previous studies showed that few cases of gallbladder NETs manifested with carcinoid syndrome [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACs have a relatively favorable prognosis, whereas tumors with squamous or neuroendocrine differentiation have a poor outcome (mean survival time, 50 vs 23 or 10 months, respectively) [ 2 , 6 ]. LCNEC has been known to exhibit aggressive behavior and early metastasis [ 4 ]. Among the previously reported LCNEC cases, 53% had directly invaded the liver at the time of diagnosis, and 47% had been identified with locoregional or distant metastases involving bone, liver or lymph nodes [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are also differences in chemotherapeutic agents between conventional AC and combined tumor of the gallbladder. Conventional AC is usually treated with gemcitabine and cisplantin, while combined ASC or NEC is treated with FOLFOX (leucovorin, fluorouracil, and oxaliplatin) or etoposide [ 4 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCNEC is a type of neuroendocrine tumour that can affect lungs, gall bladder,7 urinary bladder,8 head and neck,9 prostate,10 ovary,11 uterine cervix,12 vagina,13 endometrium,14 breast,15 colon,16 ileum,17 rectum,18 bile ducts,19 stomach,20 renal pelvis,21 skin,22 thymus,23 etc. Pulmonary neuroendocrine tumours make up to 20% of all lung cancers of which LCNEC are 10% (ie, 2–3% of all lung cancers).…”
Section: Discussionmentioning
confidence: 99%